2015
DOI: 10.5812/zjrms.17(4)2015.978
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Rural Women’s Health-Related Quality of Life and Domestic Violence

Abstract: Background:Nowadays, by development of societies, health related quality of life has become a very important issue. Traditionally for health assessment, some indexes such as; morbidity, mortality, and life expectancy, have been taken into consideration but these factors are not able to assess life satisfaction. Objectives: The present study was aimed to investigate the relationship between rural women's health-related quality of life (HRQOL) and domestic violence. Patients and Methods: This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…Sometimes these women have coldness and depression in their sex lives and never forget hate and fear of man in their family and social life. 18 , 19 Pregnancy, for various reasons, such as loss of sexual relations, misconceptions about pregnancy and abnormal sensation of husband about the pregnancy can be a point to start or intensify sexual violence against women. 20 The woman's feelings during pregnancy, vulnerability of women in this period and increasing economic pressure can be effective factors to increase violence during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes these women have coldness and depression in their sex lives and never forget hate and fear of man in their family and social life. 18 , 19 Pregnancy, for various reasons, such as loss of sexual relations, misconceptions about pregnancy and abnormal sensation of husband about the pregnancy can be a point to start or intensify sexual violence against women. 20 The woman's feelings during pregnancy, vulnerability of women in this period and increasing economic pressure can be effective factors to increase violence during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual well-being is positively associated with meaning (Rohde et al, 2017), naturalness and originality (Helminiak, 2001), life quality (Allahbakhshian et al, 2010), purpose (Ellison, 1983) and happiness (Gomez & Fisher, 2003). Smartphone addiction, which can be seen as a reflection of Internet addiction, is negatively associated with living a meaningful and purposeful life (Çevik et al, 2020;Yaran, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being is positively associated with well-being, being extraverted, happiness (Gomez & Fisher, 2003;Tanhan & Francisco, 2019), quality of life (Allahbakhshian et al, 2010;Tanhan & Strack, 2020), the spirit to fight, level of income and fatalism (Cotton et al, 1999) and sense of coherence and coping styles (Unterrainer et al, 2014). And it is negatively associated with neuroticism, psychoticism (Gomez & Fisher, 2003), the desire to die quickly, despair and suicidal thoughts (McClain et al, 2003), desperation (Cotton et al, 1999), symptoms of mental illness (Unterrainer et al, 2014), and depression (Bekelman et al, 2007;Fehring et al, 1987).…”
Section: Spiritual Well-beingmentioning
confidence: 99%
“…3 QoL is a multilevel concept, and perceived QoL refers to how people perceive and evaluate different aspects of their lives, such as marriage, interpersonal relationships, work, leisure activities, and health. 4 To improve the interventions that promote the QoL, it is necessary first to know its predictors, determinants and related factors. 5 Previous studies have suggested that personal and social factors affect the QoL, such as mental health, physical health, lifestyle, gender, marriage, nutrition, interpersonal relationships, job, and education.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, improving the QoL has been one of the main goals of development policies at the national and international levels 3 . QoL is a multilevel concept, and perceived QoL refers to how people perceive and evaluate different aspects of their lives, such as marriage, interpersonal relationships, work, leisure activities, and health 4 …”
Section: Introductionmentioning
confidence: 99%